The Influence of Self-Control and Mindfulness on Counterproductive Academic Behavior - Zainnur M. Rusdi (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2017)
Some forms of academic behavior of counter-productive that many college students are doing is plagiarism, cheating, absenteeism, and postponing the task. Counterproductive academic behavior such as plagiarism and cheating among students can be reduced if the student has self-control and good mindfulness. This study aims to examine the negative effects of self-control and mindfulness on counter-productive academic behavior. The results of hypothesis testing showed that each variable of self-control and mindfulness have positive effect on counterproductive academic behavior. The low mean value in this study indicates that the average of college students who become respondents have a low level of self-control and low mindfulness that has a tendency to perform counterproductive academic behavior.Keywords: Counterproductive Academic Behavior, Mindfulness, Self-Control